Metabolome-Based Genome-Wide Association Study Provides Genetic Insights Into the Natural Variation of Foxtail Millet - Wei, Wei; Li, Shuangdong; Wang, Yixiang; Wang, Bin; Fan, Guangyu; Zeng, Qisen; Zhao, Fang; Xu, Congping; Zhang, Xiaolei; Tang, Tang; Feng, Xiaolei; Shi, Jian; et al. (Frontiers in Plant Science, 2021)
The plant metabolome is considered as a bridge between the genome and the phenome, and is essential for the interaction between plant growth and plant-environment. Here we used LC-MS/MS method to perform widely targeted metabolomics analysis of 150 millet germplasm and simultaneous identification and quantification of 330 annotated metabolites. Comparing metabolic contents in the millets revealed significant natural variation of both primary and secondary metabolites, including flavonoids, phenolamides, hydroxycinnamoyl derivatives, nucleotides and lipids, in the millets from India, the south and north of China, among them, some of the flavonoids are the most prominent. Further digging the genetic basis of metabolites by mGWAS analysis, we found that cyanidin 3-O-glucoside and quercetin O-acetylhexside is concentratedly located at 43.55 Mb on chromosome 5 and 26.9 Mb on chromosome 7, and two Lc were mined as candidate genes, respectively. However, the signals of luteolin 7-O-glucoside and kaempferol 3-O-glucoside were also detected at 14.36 Mb on chromosome 3, and five glycosyltransferase genes on this loci were deemed to regulate their content. Our work is the first research to use mGWAS in millet and paves the way for future dissection of biosynthesis and regulation of metabolic pathways and their related complex physiological traits in millet.